Effects of High-Intensity Interval Training With Specific Techniques on Jumping Ability and Change of Direction Speed in Karate Athletes: An Inter-individual Analysis - Ojeda-Aravena, Alex; Herrera-Valenzuela, Tomás; Valdés-Badilla, Pablo; Martín, Eduardo Báez-San; Cancino-López, Jorge; Gallardo, Jairo Azócar; Zapata-Bastías, José; García-García, José Manuel (Frontiers in Physiology, 2021)
This study investigated the effect of 4-week specific technical high-intensity interval training (HIIT) on jump performance and change of direction speed (CODS) in youth karate athletes and analyzed inter-individual variability. Ten national-level athletes of both sexes (four males and six females) were randomly distributed into the experimental group (EG; n = 5) and the control group (CG; n = 5). The EG trained two to three times per week for 4 weeks applying the HIIT protocol during their usual training. The CG trained normally. Assessments included squat jump (SJ) and countermovement jump (CMJ) and CODS using the T-test. No effect and interaction of group-by-time factors were reported. Although in percentage and effect size (ES) terms increases were reported in both groups for SJ (EG: 15.2%, ES = 0.91vs. CG: 12.4%, ES = 0.02) and only in EG for the T-test (−1.7%; ES = −0.35). In turn, a trend toward a higher proportion of Responders (Rs) was observed in the EG (40% Rs) vs. CG (20% Rs) for SJ and CODS. In conclusion, the addition to regular training of a HIIT protocol with specific techniques for 4 weeks is not a sufficient stimulus to significantly increase jump performance and CODS in youth karate athletes.